2016
DOI: 10.1136/gutjnl-2016-311964
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal cell damage and systemic immune activation in individuals reporting sensitivity to wheat in the absence of coeliac disease

Abstract: ObjectiveWheat gluten and related proteins can trigger an autoimmune enteropathy, known as coeliac disease, in people with genetic susceptibility. However, some individuals experience a range of symptoms in response to wheat ingestion, without the characteristic serological or histological evidence of coeliac disease. The aetiology and mechanism of these symptoms are unknown, and no biomarkers have been identified. We aimed to determine if sensitivity to wheat in the absence of coeliac disease is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
198
1
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(216 citation statements)
references
References 46 publications
7
198
1
10
Order By: Relevance
“…Several studies have confirmed an immunologic activation in NCG/WS, [5][6][7] however, it is not known whether this is a definitive condition. 8,9 Our data show that approximately 74% of 200 patients had remained on a strict wheat-free diet for a median time of >8 years after a NCG/WS diagnosis, and they all reported that involuntary wheat consumption regularly caused symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed an immunologic activation in NCG/WS, [5][6][7] however, it is not known whether this is a definitive condition. 8,9 Our data show that approximately 74% of 200 patients had remained on a strict wheat-free diet for a median time of >8 years after a NCG/WS diagnosis, and they all reported that involuntary wheat consumption regularly caused symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the gluten-free diet has exploded in recent years, as shown both in nationally representative surveys and internet searches [9,10]. Although a subset of the population without celiac disease may develop symptoms triggered by gluten, and there are data suggestive of immune activation among that group [11], there are also a substantial number of individuals on a self-prescribed gluten-free diet who are actually reacting to fermentable oligo-, di-, monosaccharides, and polyols (FODMAPs) [12] or specifically to fructans [13]. It is also the case that a substantial number of people on a gluten-free diet have not been tested for celiac disease [14] and that upon evaluation approximately one-third of patients with a self-diagnosis of nonceliac gluten sensitivity are found to have another diagnosis in addition to, or instead of, their apparent adverse reaction to gluten; such diagnoses include intolerances to lactose or fructose, microscopic colitis, and small intestinal bacterial overgrowth [15].…”
Section: Gluten-free Dietsmentioning
confidence: 99%
“…Their indings suggested that enteropathy could occur in individuals who report GS in the absence of CD, while it is associated with increased serum antibodies recognizing bacterial lipopolysaccharide (LPS) and/or its CD14 ligand [35]. Although several antibodies were evaluated for their potential to be used as diferential diagnostic tools including anti-LPS, anti-lagellin, and anti-soluble CD14 (sCD14), the best predictive values were atributed to antibodies targeting LPS and sCD14.…”
Section: Ncgs Vs CD Microbial Signaturesmentioning
confidence: 99%
“…Based on the assumption that CD is caused by an autoimmune reaction to TG2, while NCGS is caused by chronic bacterial intestinal infections, a recent study by Columbia University Celiac Disease and Non-Celiac Gluten Sensitivityresearchers focused on the identiication of diferential, bacterial byproduct-speciic diagnostic markers to distinguish the two conditions [35]. Their indings suggested that enteropathy could occur in individuals who report GS in the absence of CD, while it is associated with increased serum antibodies recognizing bacterial lipopolysaccharide (LPS) and/or its CD14 ligand [35].…”
Section: Ncgs Vs CD Microbial Signaturesmentioning
confidence: 99%